2015
DOI: 10.1148/rg.352140114
|View full text |Cite
|
Sign up to set email alerts
|

Infiltrative Hepatocellular Carcinoma: What Radiologists Need to Know

Abstract: Hepatocellular carcinoma (HCC) is one of the leading causes of cancer-related death worldwide. The macroscopic growth pattern of HCC is subdivided into three categories: nodular, massive, and infiltrative. Infiltrative HCC accounts for 7%-20% of HCC cases and is confirmed at pathologic analysis on the basis of the spread of minute tumor nodules throughout large regions of the liver. Infiltrative HCC may represent a diagnostic challenge because it is often difficult to distinguish from background changes in cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
92
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(95 citation statements)
references
References 62 publications
0
92
0
3
Order By: Relevance
“…For this reason CT or MRI is preferred to trace the course of the SMV and SV [13] . It has been shown that PV thrombosis can results in parenchyma perfusion changes readily concealing the presence of tumor on enhanced images [14] . Hyperintensity on T2 and diffusion sequences can indicate the presence of HCC, particularly infiltrative HCC with corresponding hypointensity in comparison to liver parenchyma on T1 sequences [14] .…”
Section: Discussionmentioning
confidence: 99%
“…For this reason CT or MRI is preferred to trace the course of the SMV and SV [13] . It has been shown that PV thrombosis can results in parenchyma perfusion changes readily concealing the presence of tumor on enhanced images [14] . Hyperintensity on T2 and diffusion sequences can indicate the presence of HCC, particularly infiltrative HCC with corresponding hypointensity in comparison to liver parenchyma on T1 sequences [14] .…”
Section: Discussionmentioning
confidence: 99%
“…Uniform signal loss between dual-echo in-phase and opposed-phase gradient-echo T1-weighted MRIs suggests fat deposition. 6 …”
Section: Fatty Infiltrationmentioning
confidence: 99%
“…4 In 225 patients with HCC confirmed by pathologic analysis at liver explantation, the lesionbased sensitivity of US was only 46%. 6 Currently, all major clinical practice guidelines endorse multiphasic CT and MRI with extracellular contrast agents as first-line modalities for diagnosing and staging HCC. Both modalities provide excellent sensitivity for detecting nodular HCCs larger than 2 cm, modest sensitivity for 1-to 2-cm HCCs, and poor sensitivity for HCCs smaller than 1 cm, and it is not yet clear which modality is superior.…”
Section: Diagnosis Of Hepatocellular Carcinomamentioning
confidence: 99%
See 2 more Smart Citations